Effect of Magnetic Flux on the Quantum Transport in a Biphenyl Molecule - Dudeja, Suman; Bhattacherjee, Aranya B.; Gevorgyan, Narine (Journal of Atomic, Molecular, Condensed Matter and Nano Physics, 2014)
We report influence of magnetic flux on the quantum transport in a aromatic $π$ conjugate system made up of two phenyl rings separated by an insulator group. In the presence of a transverse magnetic field the transmission, the dipole moment and the energy of the system gives oscillatory behaviour with flux $φ$, threaded by the molecular ring showing flux quantum periodicity. This aspect may be utilized in designing nano-scale electronic devices.